Promoting active labor admission: Early labor lounge implementation barriers and facilitators from the clinician perspective. Issue 2 (19th November 2019) - Breman, Rachel B.; Low, Lisa Kane; Paul, Julie; Johantgen, Meg
Abstract: Background: The cesarean birth rate for low‐risk pregnant individuals in the United States exceeds the recommended Healthy People 2020 rate. One recommended strategy to reduce cesarean in this population is delaying hospital admission until active labor commences. A quality improvement program was implemented at a community hospital using the early labor lounge (ELL) to promote admission in active labor. This study focuses on identifying the barriers and facilitators from the clinician perspective to implementing the ELL. Methods: Interviews were conducted with a purposive sample of clinicians. Interview transcripts were open coded and themes identified inductively. A framework analysis was then conducted using the Consolidated Framework for Implementation Research (CFIR). Results: Twenty‐five staff members participated. Barriers and facilitators were identified in four of the CFIR domains. Facilitators included the strength of the evidence and the ELL itself, including the tools it contained for supporting women in latent labor. Barriers to implementation included clinician self‐efficacy and perceived low usage of the ELL. Conclusion: This analysis using, CFIR identified several barriers and facilitators to the implementation of the ELL. The context of the individual woman presenting in triage and the acceptability and self‐efficacy of the individual clinicians represented important factors for implementation.